Contacts, collisions and relationships : britons and chileans in the independence era, 1806-1831 - Baeza, Andrés, 1982- (Liverpool Latin American studies ;, 2019)
A study of the relations between Britain and Chile during the Spanish American independence era (1806-1831). It focuses on the dynamic, unpredictable and changing nature of cultural encounters to cast doubt on the assumption that imperialism was their obvious outcome and to understand further nation-building processes.